Does a picture speak louder than words? The role of infographics as a concussion education strategy. (3rd July 2019) - Provvidenza, Christine F.; Hartman, Laura R.; Carmichael, Jason; Reed, Nick
Abstract: Knowledge gaps exist regarding how to best educate audiences about concussion. Knowledge translation (KT) plays a critical role in how information is shared. In the field of concussion, infographics are becoming a popular KT strategy for synthesising and sharing information. Study objectives were to explore how infographics enhance concussion knowledge, infographic use and preferences across various stakeholders, and to determine their utility as a KT strategy. Six infographics were created to provide concussion information in a user-friendly and accessible format. A prospective design using a self-developed survey was conducted. Data were collected from youth ( n = 78) and adults ( n = 88) including students, teachers and healthcare professionals. Descriptive statistics exored perceived knowledge acquisition and infographic use. Thematic analysis of written feedback provided insight on participant responses. Participants identified that the infographics met their knowledge needs (91%) and provided them with new knowledge (87%). Participants also identified that they intend to use the infographics to build their knowledge (89%) and educate others (55%). Enhancement opportunities included incorporating graphics that appeal to different audiences and sharing the lived experiences of individuals who have a concussion. This study demonstrates the potential impact of infographics as a KT strategy that meets the knowledge needs of many audiences.